Evidence-Based Medicine: Feminist Criticisms and Implications for Women's Health - Lea Merone; Komla Tsey; Darren Russell; Andrew Daltry; Cate Nagle (Mary Ann Liebert, 2022)
Evidence-based medicine (EBM) dates back to 19th-century Paris and started out as a new paradigm for practicing medicine, with the aim of replacing anecdote with high-quality evidence from positivist-style research. Despite the clear logic underpinning EBM, there have been numerous criticisms, including maintenance of an archaic view of evidence as ?facts,? failure to acknowledge that all research is underpinned by the beliefs of the researcher, and the simple fact that medical research has historically been androcentric and results generalized to female patients. In this essay, we discuss the criticisms of EBM, with a focus on feminist critiques based on three central feminist epistemologies: feminist empiricism, standpoint theory, and social constructivism. We argue that EBM potentially perpetuates gaps in women's health and advocate for incorporating feminist epistemologies into future medical research to garner further understanding of social influences on women's health. In addition, we argue that EBM may degrade the clinical acumen and that critical thinking should become a key component of medical school curricula.